Preparing a PLC Program for the Kiln Entrance of Ceramic - A. Mutlk, Sattar (Anbar Journal of Engineering Sciences, 2009)
In the Present work, the application of the PLC in the production line was studies from the point view of industrial engineering and write program by ladder diagram (LAD) method. This study was done in ceramic factory of the state company of class and ceramic in Ramadi. It was exactly on the Kiln entrance of ceramic tiles, for reused PLC system where the tiles pieces inter the Kiln in compiled arranged rows in order to guarantees the heat distribution